Nutritional profile and its relationship with severity markers in adults with sickle cell anemia (Research, Society and Development, 2022)
Objective: To assess the nutritional profile and its relationship with the severity markers in adults with sickle cell anemia (SCA). Methodology: This is a cross-sectional, analytical study with 55 adults with SCA and 60 members of the control group. Sociodemographic, nutritional and laboratory data, as well as physical activity level were collected between March 2019 and June 2020. Mann-Whitney tests were used to compare groups and the Spearman correlation coefficient to test the relationship between variables. Results: The SCA group presented lower weight, height and body mass index. In addition, there was a positive correlation of hemoglobin and hematocrit with food intake and a negative correlation with platelets in this group. Conclusion: In light of the studied link between food intake and blood count, the importance of adequate nutritional support as part of the therapeutic management of individuals with SCA becomes evident, which impacts their prognosis.